THE ORIGIN OF THE TITLE “UTSMYI” OF KAYTAG RULERS AND THE ETYMOLOGY OF THE OECONYM “URTSMUTS” - Mammaev, Misrihan Mamaevic (History, Archeology and Ethnography of the Caucasus, 2021)
The article attempts to reveal the origin of the hereditary title “Utsmyi” of feudal rulers of Kaytag (Khaidaq’) – one of the largest state formations of the medieval Dagestan, which played an important role in political and ideological life of the North-East Caucasus. The capital of Kaytag – Qala-Quraysh (local name – “UrtsImuts”, “UrtsImutsi”), where magnificent monuments of history and culture of Medieval Age preserved, – was an administrative-political, cultural and ideological center of Dagestan. The author reviews various suggestions on the origination of the title “Utsmyi”. Interpretations of S.M. Bronevsky, E.I. Kozybsky and B.G. Malachikhanov, who suggested the origination of the title from the Arabic concept of “ismi” (notable), Jewish “otsum” (powerful, mighty), and other similar names, are considered improbable. R.M. Magomedov, B.G. Aliev, A.R. Shikhsaidov, M.S. Gadjiev suggest a feasible hypothesis about the local, Dagestan origin of the title “Utsmyi”. However, researchers of the 19th-20th centuries could not find a reliable explanation for the origin of the title in question. We propose our own view on this issue and suggest that the title “Utsmyi” derives from the local, Kaytag-Dargin colloquial name of Qala-Quraysh “UrtsImuts/UrtsImutsi”, which was recorded in written form long after the foundation of the village. The medieval Arabic written sources, local historical chronicles and epigraphic monuments, however, do not mention the local, Dagestan name “UrtsImutsi”. At the same time, the self-designated name and the name, used by the Dargins in colloquial speech since the foundation of this settlement has been and remains “UrtsImutsi”. The author explains the etymology of the oeconym from the rock massif “Urga-muza”, which means “middle mountain”, on the top (plateau) of which the village was founded long before the Arab conquests in Dagestan.
Keywords: Kaytag; feudal rulers; title “outsmyi”; origin; oeconym UrtsImuts (UrtsImutsi); etymology